Correlation of serum level of interleukin-6 and disease activity with bone-resorption activity in premenopausal rheumatoid arthritis patients - Akil, Natsir; Isbagio, H; Sumariyono, Sumariyono (Indonesian Journal of Rheumatology, 2013)
Background: Rheumatoid arthritis (RA) is a chronic, systemic disease characterized by inflammation and cellular proliferation in the synovial lining of joints that can ultimately result in cartilage and bone destruction.Patients with RA are at increased risk of osteoporotic fractures in both axial and appendicular bones. Several cytokines are involved in the pathogenesis of osteoporotic RA patients, including tumor necrosis factor Î±, interleukin (IL)-1, IL-6, and IL-17. Among these cytokines, IL-6 has a pivotal role in the pathogenesis of increased bone resorption in postmenopausal RA patients. There are currently scarce data concerning this process in premenopausal RA patients.Objective: To determine the correlation of serum level IL-6 and disease activity with bone-resorption activity in premenopausal RA patients. Methods: This is a cross-sectional study with consecutive sampling method conducted at the Division of Rheumatology, Cipto Mangunkusumo General Hospital from June until August 2010. Bone-resorption activity was quantified using serum C-terminal crosslinking telopeptide of type I collagen (CTx-I) level, while disease activity was assessed using the 28-joint disease activity (DAS28) score. Statistical analysis was performed to investigate the correlation of serum IL-6 level and disease activity with serum CTx-I level.Results: There were 38 patients enrolled in this study. Mean serum level of IL-6 was 10.99 pg/mL (SD 16.06). Mean serum level of CTx-I was 405.37 pg/mL (SD 199.32). There was no significant correlation (p = 0.252) between serum IL-6 level with serum CTx-I level;however, a significant correlation existed (r = 0.389, p = 0.033) among seropositive patients. There was no significant correlation (p = 0.257) between the DAS28score with serum CTx-I level.Conclusion: There were no significant correlation either of serum IL-6 level or disease activity with serum CTx-I level among patients in this study